Study of Precursor‐Inks Designed for High‐Quality Cu2ZnSnS4 Films for Low‐Cost PV Application. Issue 17 (1st May 2019) - Trifiletti, Vanira; Mostoni, Silvia; Butrichi, Fabio; Acciarri, Maurizio; Binetti, Simona; Scotti., Roberto
Abstract: Kesterite compound Cu2 ZnSnS4 is the most promising next leader in the chalcogenide thin films technology as it is based on earth‐abundant elements. In this work, kesterite thin films were prepared with a wet chemistry method by using a DMSO solution containing thiourea and acetylacetone, without further addition of vapour sulfur compounds to obtain the Cu2 ZnSnS4 phase. The composition and stability of the molecular precursor‐ink were investigated by EPR, IR and Raman spectroscopy. Acetate precursors were proved to have a primary role in creating a network in the sol‐gel transition by bridging the metals in solution, together with thiourea and DMSO coordination. The high‐quality of the thin films, obtained by spin coating deposition and thermal treatment at 500 °C, was assessed by XRD, Raman, Energy‐Dispersive spectroscopy and optical analysis, which revealed a direct band gap of 1.5 eV. Therefore, the precursor‐ink and the deposition process developed in this work are very well suitable for solar cell application. Abstract : Cu2 ZnSnS4 thin films were synthesized by sol‐gel, without the addition of vapour sulfur compounds to obtain kesterite. Acetate precursors have the main role in creating a network, by bridging the metals in solution, together with thiourea and DMSO coordination. The precursor‐ink and the deposition process are well suitable for photovoltaic applications.